Active Site Gate Dynamics Modulate the Catalytic Activity of the Ubiquitination Enzyme E2-25K - Manoj K. Rout (Nature Portfolio, 2018)
Abstract The ubiquitin proteasome system (UPS) signals for degradation of proteins through attachment of K48-linked polyubiquitin chains, or alterations in protein-protein recognition through attachment of K63-linked chains. Target proteins are ubiquitinated in three sequential chemical steps by a three-component enzyme system. Ubiquitination, or E2 enzymes, catalyze the central step by facilitating reaction of a target protein lysine with the C-terminus of Ub that is attached to the active site cysteine of the E2 through a thioester bond. E2 reactivity is modulated by dynamics of an active site gate, whose central residue packs against the active site cysteine in a closed conformation. Interestingly, for the E2 Ubc13, which specifically catalyzes K63-linked ubiquitination, the central gate residue adopts an open conformation. We set out to determine if active site gate dynamics play a role in catalysis for E2-25K, which adopts the canonical, closed gate conformation, and which selectively synthesizes K48-linked ubiquitin chains. Gate dynamics were characterized using mutagenesis of key residues, combined with enzyme kinetics measurements, and main chain NMR relaxation. The experimental data were interpreted with all atom MD simulations. The data indicate that active site gate opening and closing rates for E2-25K are precisely balanced.